Systematic review of the evidence on the effectiveness of sexual and reproductive health interventions in humanitarian crises. Issue 12 (18th December 2015) - Warren, Emily; Post, Nathan; Hossain, Mazeda; Blanchet, Karl; Roberts, Bayard
Abstract : Objectives: This systematic review aims to evaluate evidence on the effectiveness of sexual and reproductive health (SRH) interventions delivered in humanitarian crises. Setting: Crisis affected low-income or middle-income countries. Participants: Crisis-affected populations in low-income or middle-income countries. Method: Peer-reviewed and grey literature sources were systematically searched for relevant papers detailing interventions from 1 January 1980 until the search date on 30 April 2013. Data from included studies were then extracted, and the papers' quality evaluated using criteria based on modified STROBE and CONSORT checklists. Primary and secondary outcome measures: Primary outcomes include, but are not limited to, changes in morbidity, mortality, sexually transmitted infection (STI) diagnosis or gender-based violence. Secondary outcomes include, but are not limited to, reported condom use or skilled attendance at birth. Primary outputs include, but are not limited to, condoms distributed or education courses taught. Results: Of 7149 returned citations, 15 studies met the inclusion criteria. Only one randomised controlled trial was identified. The remaining observational studies were of moderate quality, demonstrating limited use of controls and inadequate attempts to address bias. Evidence of effectiveness was available for the following interventions: impregnated bed nets for pregnant women, subsidised refugee healthcare, female community health workers, and tiered community reproductive health services. Conclusions: The limited evidence base for SRH interventions highlights the need for improved research on the effectiveness of public health interventions in humanitarian crises. While interventions proven efficacious in stable settings are being used in humanitarian efforts, more evidence is required to demonstrate the effectiveness of delivering and scaling-up such interventions in humanitarian crises.